Report on proposed new interior design scheme of Lonsdale Retail Store for TNT Kickboxing at Lot 322-324 Level 3, Ramlee Mall, Suria KLCC, Kuala Lumpur / Faizol Awang - Awang, Faizol (Faculty of Architecture, Planning and Surveying, 2010)
The competitive environment in apparel retail store is expected to get more intense. There are lot of other retails have been set up in every states in Malaysia and more are still to come. To succeed in this business, retailers will have to rethink their existing work practices and business strategies to see if more efficiencies and competitive advantage can be secured by doing things differently. This proposal is to proposed new interior design scheme of Lonsdale retail store for TNT Kickboxing at Lot 322-324 level 3 Ramlee Mall, Suria KLCC Kuala Lumpur. The main objective is to introduce a ‘Bold and beautiful’ concept and ‘Modem’ design to follow the client corporate image and identity. This retail is different from other retail. It will be a target place for the Lonsdale fans and lovers, it will act as a catalyst to prompt other retailers to convert a conventional setting to the current modem concept store. The idea to undertake this project was given due attention after taking into consideration the current and design issues, and to solve the problems encountered by the other retails efficiently. Therefore, a plan was proposed to prepare new design and approach that may interest and fulfil the aspiration of the client, workers and customer. Design scheme concept should be taken into account as profoundest study. From the research and observation conducted, all data and details gathered was used as a guideline in the design process.